2002
DOI: 10.1038/416723a
|View full text |Cite|
|
Sign up to set email alerts
|

Origins and estimates of uncertainty in predictions of twenty-first century temperature rise

Abstract: Predictions of temperature rise over the twenty-first century are necessarily uncertain, both because the sensitivity of the climate system to changing atmospheric greenhouse-gas concentrations, as well as the rate of ocean heat uptake, is poorly quantified and because future influences on climate-of anthropogenic as well as natural origin-are difficult to predict. Past observations have been used to help constrain the range of uncertainties in future warming rates, but under the assumption of a particular sce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
233
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 321 publications
(247 citation statements)
references
References 23 publications
14
233
0
Order By: Relevance
“…Warming as high as 6.9 K (relative to 1990s temperatures) cannot be ruled out at the 95% confidence level in the SRES A1FI scenario (figure 6). Stott & Kettleborough (2002) also showed that as the signal of climate strengthens, the uncertainty in future temperature rise is likely to reduce, potentially halving uncertainties in late twenty-first century warming by 2020 when compared with values estimated in 2000 ( figure 6). The range of warming under the B2 scenario is 1.6-3.7 K by the 2090s decade relative to the 1990s decade.…”
Section: Constraints On Future Climate Change Based On Past Climate Cmentioning
confidence: 99%
See 3 more Smart Citations
“…Warming as high as 6.9 K (relative to 1990s temperatures) cannot be ruled out at the 95% confidence level in the SRES A1FI scenario (figure 6). Stott & Kettleborough (2002) also showed that as the signal of climate strengthens, the uncertainty in future temperature rise is likely to reduce, potentially halving uncertainties in late twenty-first century warming by 2020 when compared with values estimated in 2000 ( figure 6). The range of warming under the B2 scenario is 1.6-3.7 K by the 2090s decade relative to the 1990s decade.…”
Section: Constraints On Future Climate Change Based On Past Climate Cmentioning
confidence: 99%
“…For example, introducing a new model into the analysis that has a lower sensitivity than other models has only a second-order effect on the result (Stott et al 2006b). At the same time, uncertainty is reduced in a predictable way as the signal strengthens (Stott & Kettleborough 2002). For a STAID forecast, there should be a transfer function that links a forecast quantity to an observable quantity.…”
Section: Constraints On Future Climate Change Based On Past Climate Cmentioning
confidence: 99%
See 2 more Smart Citations
“…Forest et al 2000) or by generating 'pseudo-ensembles' by rescaling the output of a single atmosphere-ocean general circulation model (AOGCM; Allen et al 2000;Stott & Kettleborough 2002). This is limited, however, to predicting uncertainty ranges on just a few global climate variables.…”
Section: Introductionmentioning
confidence: 99%